Orientasi pola komunikasi kekeluargaan terhadap sahsiah remaja - Nor Mukmin, Mahmood (2019)
The failure of family communication is often associated with adolescent involvement in social problems. In this context, family communication plays an important role in order to help the adolescent with good personality. Previous studies, stated that family communication practice plays role in developing personality of adolescent. The involvement of adolescents with social problems shows that they have a personality problem. Therefore, this study aims to identify the relationship between family communication patterns toward the development of the adolescent’s personality. Relying on the Family Communication Patterns Theory (FCPT), this study examines the family communication patterns, which is the conversation orientation and conformity orientation, type of family practice in the adolescent’s family, personality of adolescent, difference between the adolescent moral based on respondent’s demography and also to identify the relationship between family communication orientation patterns and adolescent’s personality. Data collection was done by a questionnaire that has been individually responded by the adolescent. The instrument used to measure the patterns of family communication was adapted from Ritchie and Fitzpatrick (1990) and Aziyah and friends (2016). Meanwhile, the instrument to measure the personality of the adolescent in adapted from Islamic Spiritual Intelligence by Zanariah and Ishak (2015). A total of 400 students from Sekolah Menengah Kebangsaan (SMK) and Sekolah Yayasan Islam Kelantan (SYIK) in Kota Bharu, Kelantan were involved in this study. The data collected was analyzed using descriptive and inferential statistics. The result of the study found that the conversation orientation patterns of family communication are higher than conformity orientation, while the type of family practiced is consensual family. Furthermore, this study found that there is a significant and positive relationship between the patterns of family communication and adolescent personality. Consequently, this study provide empirical evidence to the FCPT. This research also give suggestion to family about family communication patterns which can be practiced in developing adolescent personality.